In situ Adipogenesis in Biomaterials Without Cell Seeds: Current Status and Perspectives - Yang, Jiqiao; Zhou, Chen; Fu, Jingyang; Yang, Qianru; He, Tao; Tan, Qiuwen; Lv, Qing (Frontiers in Cell and Developmental Biology, 2021)
For cosmetic and reconstructive purposes in the setting of small-volume adipose tissue damage due to aging, traumatic defects, oncological resections, and degenerative diseases, the current strategies for soft tissue replacement involve autologous fat grafts and tissue fillers with synthetic, bioactive, or tissue-engineered materials. However, they all have drawbacks such as volume shrinkage and foreign-body responses. Aiming to regenerate bioactive vascularized adipose tissue on biomaterial scaffolds, adipose tissue engineering (ATE) has emerged as a suitable substitute for soft tissue repair. The essential components of ATE include scaffolds as support, cells as raw materials for fat formation, and a tolerant local environment to allow the regeneration to occur. The commonly loaded seeding cells are adipose-derived stem cells, which are expected to induce stable and predictable adipose tissue formation. However, defects in stem cell enrichment, such as donor-site sacrifice, limit their wide application. As a promising alternative approach, cell-free bioactive scaffolds recruit endogenous cells for adipogenesis. In biomaterials without cell seeds, the key to sufficient adipogenesis relies on the recruitment of endogenous host cells and continuous induction of cell homing to scaffolds. Regeneration, rather than repair, is the fundamental dominance of an optimal mature product. To induce in situ adipogenesis, many researchers have focused on the mechanical and biochemical properties of scaffolds. In addition, efforts to regulate an angiogenic and adipogenic microenvironment in cell-free settings involve integrating growth factors or extracellular matrix proteins onto bioactive scaffolds. Despite the theoretical feasibility and encouraging results in animal models, few of the reported cell-free biomaterials have been tested in humans, and failures of decellularized adipose tissues in adipogenesis have also been reported. In these cases, the most likely reason was the lack of supporting vasculature. This review summarizes the current status of biomaterials without cell seeds. Related mechanisms and influencing factors of in situ adipogenesis in cell-free biomaterials, dilemma in the development of biomaterials, and future perspectives are also addressed.